Migrationsformen im Nomadenrandgebiet von Südwest-Iran - Ehrmann, Dieter (ERDKUNDE, 1974)
Between the mountain-nomadism of the Central Zagros and the people with a settled way of life on the Iranian Highland exists a region of transition, in which several forms of regional mobility have developed. The migrations of the different groups are the manifestation of different forms of life and economy. Whereas migration in order to earn a living forms the common characteristic of all groups, the economy varies between cattle-breeding, agriculture and handicrafts. Through this there are also changes in the way of life. The seasonally inhabited tent loses its importance. But even in this relatively small region there are other forms of regional mobility, for example the seasonal migration of merchants. The four discussed examples try to show the complexity of the migration-forms on the periphery of a nomadic region.